What drives flight to quality?. (7th December 2017) - Opitz, Sebastian; Szimayer, Alexander
Abstract: The returns of equities and bonds tend to be positively correlated, but in extreme situations this relation reverses. Large negative equity returns co‐occur with large positive bond returns. This is potentially caused by investors reassessing their risk preferences and shifting their wealth to less risky asset classes, which is frequently termed flight to quality. We examine macroeconomic factors to identify the driving variables using a conditional copula model. Analysing quarterly data from 1952 to 2014, we find that the Treasury bill rate is the most significant driver. This insight is useful for asset allocation and risk management.